KARAKTERISTIK KEPEMIMPINAN UMAR BIN KHATTAB DAN RELEVANSINYA TERHADAP PRINSIP GOOD GOVERNANCE - Syahfitri, Imeldha; Nurzena (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the leadership characteristics of Umar bin Khattab and examine their relevance to the principles of good governance in the context of modern leadership. The background of this study is based on the phenomenon of leadership crisis characterized by low transparency, accountability, and justice in current leadership practices. The research method used is a qualitative approach with library research, through analysis of historical sources and relevant literature. The results of the study indicate that the leadership characteristics of Umar bin Khattab include fairness, firmness, responsibility, simplicity, and closeness to the people. These characteristics are reflected in various policies and actions taken during his reign. Furthermore, these characteristics have a strong relevance to the principles of good governance, such as transparency, accountability, justice, and effectiveness in government management. Thus, the leadership of Umar bin Khattab can be used as an alternative model in building modern leadership with integrity and oriented towards the welfare of society.